2005
DOI: 10.1191/0267659105pf788oa
|View full text |Cite
|
Sign up to set email alerts
|

Dextran sulfate as a leukocyte-endothelium adhesion molecule inhibitor of lung injury in pediatric open-heart surgery

Abstract: The data suggeste the possible effects of dextran sulfate in ameliorating post-perfusion lung damage by interfering with leukocyte-endothelial cell adhesion in pediatric open-heart operations. Future application to patients with more complex anomalies is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…No toxic effect of DSS on the lungs has been reported. On the contrary, it has been reported that DSS prevents pulmonary capillary pressure changes, and DSS has even been used in open heart surgery to prevent lung injury in recent years, with successful results [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…No toxic effect of DSS on the lungs has been reported. On the contrary, it has been reported that DSS prevents pulmonary capillary pressure changes, and DSS has even been used in open heart surgery to prevent lung injury in recent years, with successful results [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preservation of perioperative RV function by DXS may be central to ensure optimal postoperative recovery. Indeed, the use of DXS (MW 8000) during CPB in a pediatric population has been shown to ameliorate immediate post-CPB respiratory index [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DXS in part improved the hemodynamic situation by ameliorating diastolic LV function and RV-and pulmonary artery pressures post-CPB. Whilst DXS has been used in a few patient trials [25], including CPB in children, [15] larger randomized clinical trials would be needed before judging the possible importance of the use of DXS in altering current clinical practice. However, in light of the fact that DXS at the current dose was not associated with any adverse events and was well tolerated, it remains to be substantiated whether a more aggressive treatment regimen, evaluated in a longer post-CBP follow-up and ultimately analyzed in human trials, may more markedly and sustainably improve post-CPB cardiac function and outcome.…”
Section: Study Limitationsmentioning
confidence: 99%
“…104 It was also found to improve significantly post-CPB respiratory index in pediatric patients. 105 Continuous ultrafiltration during CPB decreases pulmonary edema and improves lung function through increasing pCOP as well as removing inflammatory mediators. 45 Methods such as RAP and colloidal prime have also been found to minimize EVLW following CPB.…”
Section: Pulmonary Edemamentioning
confidence: 99%